Peran Sumber Pelayanan dan Jenis Provider Terhadap Diskontinuitas Kontrasepsi: Analisis Data SDKI 2012 - Izzatul Arifah; Sukamdi Sukamdi; Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2016)
Effects of health facility ownership and type of providers on contraception discontinuation: an analysis of 2012 Indonesian demographic health surveyPurposeThis study aimed to examine the role of source of family planning services and types of providers on the discontinuity pattern of modern contraceptive use in women of childbearing age.MethodsThis study analyzed the longitudinal data using secondary data of the IDHS 2012. The sample criteria were: women ever married, aged 15-49, who have ever used modern contraception (pills, injections, IUDs and implants). Stratified Cox models were used to assess the effect of predictors toward contraceptive discontinuation.ResultsKaplan-Meier curves showed higher discontinuity in the short-term contraceptive methods such as injections and pills. Multivariable analysis showed the influence of method source to discontinuation after controlling for other factors, namely age, number of children, education level and place of residence. The risk of discontinuation was greater in government source than private, with HR 1.14 95% CI (1.06 to 1.23). Sub-sample analysis of private services showed a greater chance of discontinuity in physician, with HR 1.28 95% CI (1.06 to 1.54).ConclusionContraceptive discontinuation rate was lower among women using private source and midwives. Women with older age had greater number of children, and the factor of low education levels also was associated with longer duration of contraceptive use.